Code of conduct for responsible fisheries (FAO RomeIT, 1995)
Provides principles and standards applicable to the conservation, management and development of all fisheries. Covers the capture, processing and trade of fish and fishery products, fishing operations, aquaculture, fisheries research and the integration of fisheries into coastal area management.
DC